SOSIALISASI PERAN LATIHAN LUTUT BAGI LANSIA DENGAN OSTEOARTHRITIS (OA) DI POLIKLINIK REHABILITASI MEDIK, RSUD KOTA MATARAM, NUSA TENGGARA BARAT - Permana Putra, I Gede Ari; Anulus, Ayu; Verra, Verra; Dwiyani, Lili (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Osteoarthritis (OA) is a common health problem experienced by the elderly. OA or bone calcification is a health problem in the form of joint calcification due to cartilage damage. The prevalence of OA in Indonesia continues to increase along with the increasing age of the population and of course this has a major impact on the daily activities of the elderly. proposed to prevent osteoarthritis and control the development of the disease, one of which is with simple medical rehabilitation therapy at home. There are still many elderly who do not understand the importance of implementing simple medical rehabilitation therapy at home. The purpose of this community service is to increase knowledge through the socialization of medical rehabilitation therapy at home for the elderly with OA. The methods of community service are socialization, simulation, and discussion. The results of the service show that elderly patients actively ask questions, pay attention to socialization, and some patients demonstrate stretching techniques. The conclusion is that the socialization of medical rehabilitation therapy at home for the elderly with OA has been carried out well.